Effects of cement-curing mode and light-curing unit on the bond durability of ceramic cemented to dentin - Sheila Pestana Passos; Rodrigo Othávio Assunção Souza; Silvia Masae Araújo Michida; Sandra Costa Zamboni; Simone Helena Gonçalves de Oliveira (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this study was to evaluate the effects of different light-curing units and resin cement curing types on the bond durability of a feldspathic ceramic bonded to dentin. The crowns of 40 human molars were sectioned, exposing the dentin. Forty ceramic blocks of VITA VM7 were produced according to the manufacturer's recommendations. The ceramic surface was etched with 10% hydrofluoric acid / 60s and silanized. The dentin was treated with 37% phosphoric acid / 15s, and the adhesive was applied. The ceramic blocks were divided and cemented to dentin according to resin cement / RC curing type (dual- and photo-cured), light-curing unit (halogen light / QTH and LED), and storage conditions (dry and storage / 150 days + 12,000 cycles / thermocycling). All blocks were stored in distilled water (37°C / 24h) and sectioned (n = 10): G1 - QTH + RC Photo, G2 - QTH + RC Dual, G3 - LED + RC Photo, G4 - LED + RC Dual. Groups G5, G6, G7, and G8 were obtained exactly as G1 through G4, respectively, and then stored and thermocycled. Microtensile bond strength tests were performed (EMIC), and data were statistically analyzed by ANOVA and Tukey's test (5%). The bond strength values (MPa) were: G1 - 12.95 (6.40)ab; G2 - 12.02 (4.59)ab; G3 - 13.09 (5.62)ab; G4 - 15.96 (6.32)a; G5 - 6.22 (5.90)c; G6 - 9.48 (5.99)bc; G7 - 12.78 (11.30)ab; and G8 - 8.34 (5.98)bc. The same superscript letters indicate no significant differences. Different light-curing units affected the bond strength between ceramic cemented to dentin when the photo-cured cement was used, and only after aging (LED > QTH). There was no difference between the effects of dual- and photo-cured resin-luting agents on the microtensile bond strength of the cement used in this study.